Thermal degradation of poly(phenacyl methacrylate) - Soykan, C; Ahmedzade, M (Elsevier Sci Ltd, 2002)
The thermal degradation of poly(phenacyl methacrylate) [poly(PAMA)] has been studied using a system consisting of a degradation tube, with a condenser for product collection, a gas phase IR cell and a rotary pump and by thermogravimetry (TG). Investigation of the nature of the evolved products has been supplemented by studies of structural changes in the degrading polymer by FT-IR spectroscopy. Changes have been investigated under programmed heating at 10 degreesC/min from room temperature to 500 degreesC. In degradation of poly(PAMA), product identification studies were done using FT-IR, H-1- and C-13-NMR and gas chromatography-mass spectroscopy techniques. Depolymerization is the main reaction in thermal degradation of the polymer. The degradation produces anhydride ring structures in the chain at temperatures above 300 degreesC. Total degradation to 430 degreesC produces many volatile product such as the monomer, acetophenone, benzaldehyde and others. A mechanism of degradation showing the formation of some of these products is discussed. The activation energy for the thermal degradation of poly(PAMA) is 89.2 kJ/mol in the first stage observed at 207-300 degreesC. The second stage decomposition commenced at 300-430 degreesC and the energy of activation was 66.9 kJ/mol. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: poly(phenacyl methacrylate); thermal degradation; activation energies